Topically Applied Etamsylate: A New Orphan Drug for HHT-Derived Epistaxis (Antiangiogenesis through FGF Pathway Inhibition) - Albiñana, Virginia; Giménez-Gallego, Guillermo; García-Mato, Angela; Palacios, Patricia; Recio-Poveda, Lucia; Cuesta, Angel-M; Patier, José-Luis; Botella, Luisa-María (TH Open, 2019)
Hereditary hemorrhagic telangiectasia (HHT) is a vascular dysplasia characterized by recurrent and spontaneous epistaxis (nose bleeds), telangiectases on skin and mucosa, internal organ arteriovenous malformations, and dominant autosomal inheritance. Mutations in Endoglin and ACVRL1/ALK1, genes mainly expressed in endothelium, are responsible in 90% of the cases for the pathology. These genes are involved in the transforming growth factor-β(TGF-β) signaling pathway. Epistaxis remains as one of the most common symptoms impairing the quality of life of patients, becoming life-threatening in some cases. Different strategies have been used to decrease nose bleeds, among them is antiangiogenesis. The two main angiogenic pathways in endothelial cells depend on vascular endothelial growth factor and fibroblast growth factor (FGF). The present work has used etamsylate, the diethylamine salt of the 2,5-dihydroxybenzene sulfonate anion, also known as dobesilate, as a FGF signaling inhibitor. In endothelial cells, in vitro experiments show that etamsylate acts as an antiangiogenic factor, inhibiting wound healing and matrigel tubulogenesis. Moreover, etamsylate decreases phosphorylation of Akt and ERK1/2. A pilot clinical trial (EudraCT: 2016–003982–24) was performed with 12 HHT patients using a topical spray of etamsylate twice a day for 4 weeks. The epistaxis severity score (HHT-ESS) and other pertinent parameters were registered in the clinical trial. The significant reduction in the ESS scale, together with the lack of significant side effects, allowed the designation of topical etamsylate as a new orphan drug for epistaxis in HHT (EMA/OD/135/18).
Keywords: HHT; Endoglin; Alk1; antiangiogenesis; etamsylate; epistaxis; FGF pathway; TGF-β signaling pathway